DDDR-23. COMBINATION THERAPY WITH PACLITAXEL, CARBOPLATIN, AND LOW-INTENSITY ULTRASOUND FOR RECURRENT GLIOBLASTOMA: RATIONALE FOR ONGOING PHASE II CLINICAL TRIAL - Habashy, Karl; Dmello, Crismita; Chen, Li; Arrieta, Victor; Kim, Kwang-Soo; Gould, Andrew; Bouchoux, Guillaume; Canney, Michael; Stupp, Roger; Sonabend, Adam (Neuro-oncology (Charlottesville, Va.), 2023)
We recently participated in phase 1/2 clinical trials where patients with recurrent glioblastoma received surgery for tumor resection followed by implantation of an ultrasound device into a skull window for subsequent repeated blood-brain barrier opening and concomitant delivery of chemotherapy (Sonabend et al., Lancet Oncology). Intraoperative experiments demonstrated a 3.7 to 5.9-fold increase in the brain concentration of paclitaxel (NCT04528680) and carboplatin (NCT03744026). Building on the pharmacokinetics and safety of these trial results, and the historical use of paclitaxel and carboplatin as a combination in other cancers, we investigated the efficacy of this combination in glioblastoma models. First, we analyzed the cytotoxicity of both drugs in vitro against five human cell lines and six patient-derived xenografts as monotherapy and in combination at concentrations derived from our human intraoperative pharmacokinetic studies. Cell lines exhibited little overlap in susceptibility to the drugs, with 27% being exclusively susceptible to one of the two drugs tested. The combination covered 81% of cell lines, compared to 54% covered with monotherapy. We also assessed for synergy using the Loewe model and recorded synergy in 55% of cells. We then evaluated the benefit of this combination in vivo in two xenograft models (MES83 and GBM6) where drugs were administered with ultrasound. Combination therapy proved more effective than monotherapy with either of the drugs, led to distinct effects on cell cycle progression and enhanced DNA damage and apoptosis. We conclude that the addition of carboplatin to paclitaxel may be more effective than monotherapy with paclitaxel, which we performed in our phase 1 trial. This combination is supported by its efficacy in other cancers, and the synergy and independent susceptibility to each drug in glioma models. The safety and efficacy of this approach are currently under investigation in an ongoing phase II trial for patients with recurrent GBM (NCT04528680).